Variables with prognostic value in the onset of idiopathic sudden sensorineural hearing loss - Bogaz,Eduardo Amaro (2015)
ABSTRACT INTRODUCTION: The establishment of an individualized prognostic evaluation in patients with a diagnosis of idiopathic sudden sensorineural hearing loss (ISSHL) remains a difficult and imprecise task, due mostly to the variety of etiologies. Determining which variables have prognostic value in the initial assessment of the patient would be extremely useful in clinical practice. OBJECTIVE: To establish which variables identifiable at the onset of idiopathic sudden sensorineural hearing loss have prognostic value in the final hearing recovery. METHODS: Prospective, longitudinal cohort study. Patients with ISSHL followed by the Department of Otology-Neurotology of a quaternary hospital were included. The following variables were evaluated and correlated with final hearing recovery: age, gender, vertigo, tinnitus, initial degree of hearing loss, contralateral ear hearing, and elapsed time to treatment. RESULTS: 127 patients with ISSHL were evaluated. Rates of absolute and relative recovery were 23.6 dB and 37.2% respectively. Complete hearing improvement was observed in 15.7% patients; 27.6% demonstrated significant improvement and improvement was noted in 57.5%. CONCLUSION: During the onset of ISSHL, the following variables were correlated with a worse prognosis: dizziness, profound hearing loss, impaired hearing in the contralateral ear, and delay to start treatment. Tinnitus at the onset of ISSHL correlated with a better prognosis.